Participatory variety selection of improved finger millet [Eleusine coracana (L.) Gaertn.] varieties at Debube Ari District, South Omo Zone, Southern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
Finger millet is staple food crop in drought-prone areas of the world and often considered as a component of food security strategies in Ethiopia. However, its yield is low in South Omo zone due to different production problems such as lack of improved varieties, lodging, and moisture stress in dry areas. A participatory finger millet variety selection was conducted at Kaysa, Baytesimal and Alga kebeles of Debube Ari District, South Omo Zone during the 2019-cropping season to identify high yielding finger millet variety/varieties .The field experiments was laid out in a randomized complete block design with three replications. The combined analysis’s of variance results revealed that there were significant (p